2017
DOI: 10.1177/0361684317718505
|View full text |Cite
|
Sign up to set email alerts
|

The Femininity–Money Incongruity Hypothesis

Abstract: Women are often stereotyped as poorly equipped to deal with money matters, compared to men, yet very little research has examined the underpinnings and consequences of such gender stereotypes. Drawing on descriptive and prescriptive elements of women's social roles, we empirically examined the gendered nature of money stereotypes. Specifically in the current work, we introduced and investigated the femininity-money incongruity hypothesis, which suggests that when the concepts of femininity and money are both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Moreover, money attitudes have a greater impact on women's financial capability and management skills than men's (Falahati & Sabri, 2015; Sabri et al, 2017). Past research also suggests that money is sometimes perceived as incongruent with the idea of femininity, having a detrimental effect on cognitive performance (Allen & Gervais, 2017). Nevertheless, it is worth pointing out that a few exceptions also exist in this case: Bonsu (2008), Lim et al (2003) and Rimple (2020) found a higher tendency to feel anxiety and a lower sense of confidence in relation to money, respectively, in Ghanaian, Singaporean, and Indian males than in their female counterparts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, money attitudes have a greater impact on women's financial capability and management skills than men's (Falahati & Sabri, 2015; Sabri et al, 2017). Past research also suggests that money is sometimes perceived as incongruent with the idea of femininity, having a detrimental effect on cognitive performance (Allen & Gervais, 2017). Nevertheless, it is worth pointing out that a few exceptions also exist in this case: Bonsu (2008), Lim et al (2003) and Rimple (2020) found a higher tendency to feel anxiety and a lower sense of confidence in relation to money, respectively, in Ghanaian, Singaporean, and Indian males than in their female counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…In the field of gender differences in money‐related contexts, insights on how gender stereotypes affect the gender pay gap, leadership positions in the financial industry, financial literacy, and activities in high finance have already been investigated (e.g., Capelle‐Blancard & Reberioux, 2021; Tinghög et al, 2021; Williams et al, 2010). In particular, Allen and Gervais (2017) have analysed how gender stereotypes affect women, suggesting that money is incompatible with the stereotypic female gender identity, with detrimental cognitive costs for women as they navigate gender roles. Nevertheless, the specific contents of stereotypes related to gender and money have not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remainder of the articles in this subdomain reported miscellaneous findings linking ambivalent sexism to various stereotype-related outcomes (J. Allen & Gervais, 2017;Carter et al, 2006;Meagher, 2017;Zell et al, 2016). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Stereotypical Perceptions and Behavior (N Articles = 17)mentioning
confidence: 99%